REPRODUCTIVE BIOLOGY OF THE FRESHWATER CLAM POKEA (Batissa violacea var. celebensis, VON MARTEN 1897) (Bivalvia: Corbiculidae) IN THE POHARA RIVER, SOUTHEAST SULAWESI, INDONESIA - Bahtiar, Bahtiar; Anadi, La; Nurgayah, Wa; Hamzah, Muhaimin; Hernawan, Udhi Eko (BIOTROPIA, 2021)
The freshwater clam, locally known as Pokea, (Batissa violacea var celebensis, von Martens 1897; Bivalvia: Corbulidae) is a popular and widely consumed food in Kendari, Southeast Sulawesi. Despite its popularity, basic information required for conservation managenment, such as reproductive biology, is lacking. This study aims to examine the reproductive biology of the clam obtained from the Pohara River, Kendari. Pokea samples were collected monthly from February 2012 to January 2013. We recorded parameters of reproductive biology, including sex ratio, stage of gonadal maturity, gonadosomatic index (GSI), fecundity, and size of the first mature gonad from each sample. Data were analysed using chi-square test and linear regression in the package Sigma Plot v.6.0. Pokea population in the Pohara River was male-biased. The population spawns throughout the year and the peak spawning season was August-September. Mature gonad was found at small shell size (indicating early sexual maturity). Food availability might have influenced the gonadal development in Pokea. This baseline information is very relevant for conservation practices of Pokea population in the Pohara River.